Predation impacts of invasive raccoons on rare native species - Oe, Sakura (Sci Rep, 2020)
In Japan, there are concerns that invasive alien raccoons prey on rare native species during their spawning season from late winter to early summer. We investigated raccoon predation impact by examining the predation presence using DNA metabarcoding and extent of predation on rare native species using stable isotope analysis. We captured raccoons in Hokkaido, Japan from April to August in 2018 and 2019. We analysed raccoon faeces and gastric contents by DNA metabarcoding to detect the rare native Hokkaido salamander and Japanese crayfish. Hokkaido salamanders were detected from gastric contents, but Japanese crayfish were not detected in any samples. Stable isotope analysis of raccoon muscle samples and the Bayesian mixing model were used to estimate each food resource’s contribution to the raccoon diet. Animal food resources accounted for 70% of total consumed food. The foraging ratios of amphibians and crustaceans were about 9% and 5%, respectively. Raccoons have been found to use amphibians at a higher rate than previously reported, including a rare endangered species, the Hokkaido salamander. Hokkaido salamander and Japanese crayfish spawn in the spring, and increased predation pressure by raccoons may directly impact populations of these rare native species.